2013
DOI: 10.1002/jgrd.50394
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of nocturnal low‐level jets over North Africa and implications for modeling mineral dust emission

Abstract: [1] This study presents the first climatology for the dust emission amount associated with Nocturnal Low-Level Jets (NLLJs) in North Africa. These wind speed maxima near the top of the nocturnal boundary layer can generate near-surface peak winds due to shear-driven turbulence in the course of the night and the NLLJ breakdown during the following morning. The associated increase in the near-surface wind speed is a driver for mineral dust emission. A new detection algorithm for NLLJs is presented and used for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
247
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 141 publications
(267 citation statements)
references
References 85 publications
20
247
0
Order By: Relevance
“…Other external driving data sets, e.g. potential dust sources, are chosen as in previous studies (summarized above, Fiedler et al 2013Fiedler et al , 2014Heinold et al 2013) and are the same for all offline calculations. This approach allows to assign differences in the offline dust emission calculations to the wind speed.…”
Section: Dust Emissionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other external driving data sets, e.g. potential dust sources, are chosen as in previous studies (summarized above, Fiedler et al 2013Fiedler et al , 2014Heinold et al 2013) and are the same for all offline calculations. This approach allows to assign differences in the offline dust emission calculations to the wind speed.…”
Section: Dust Emissionmentioning
confidence: 99%
“…The diurnal cycle of dust emission from H2ES-I, T-H2ES-O and T-EI-O as well as box-and-whisker plots of the near-surface wind speed from HadGEM2-ES and ERAInterim forecasts seasonally averaged for 1980-2009 are analyzed for the sub-domains S1 over parts of West Africa and S3 enclosing the Bodélé Depression. The geographical location of these sub-domains follows the definition in Fiedler et al (2013) and are shown in Fig. 4.…”
Section: Diurnal Cyclementioning
confidence: 99%
See 3 more Smart Citations